European environmental law - Kingston, Suzanne, 1977- (Cambridge University Press, 2017)
EU Environmental Law is a critical, comprehensive and engaging account of the essential and emerging issues in European environmental law and regulation today. Suitable for advanced undergraduate and postgraduate students, the book delivers a thematic and contextual treatment of the subject for those taking courses in environmental law, environmental studies, regulation and public policy, and government and international relations. Placing the key issues in context, EU Environmental Law takes an interdisciplinary and thematic approach to help students to better understand the implementation and enforcement of environmental law and policy across Europe. It offers an accessible overview, and links theory with practical applications that will allow students to contextualise the outcomes of legal rules and their impact on public and private behaviours. It provides a definitive account of the subject, examining traditional topics such as nature conservation law, waste law and water law, alongside increasingly important fields such as the law of climate change, environmental human rights law, and regulation of GMOs and nanotechnology.